Effect of Ti addition on density and microstructure development of MoSiBTiC alloy. Issue 1760 (12th January 2015) - Baker, I.; Heilmaier, M.; Kishida, K.; Mills, M.; Miura, S.; Kim, Joung Wook; Yoshimi, Kyosuke; Katsui, Hirokazu; Goto, Takashi
ABSTRACT The effect of Ti addition on the density and microstructure development of MoSiBTiC alloy was investigated. Two kinds of MoSiBTiC alloys with the composition of Mo-5Si-10B-10Ti-10C (10Ti alloy) and Mo-5Si-10B-15Ti-10C (15Ti alloy) (at. %) were prepared by conventional arc-melting. The primary phase of as-cast 10Ti and 15Ti alloys was (Ti, Mo)C, and there were two eutectic phases of Moss + (Ti, Mo)C and Moss + T2 + (Ti, Mo)C in the alloys. In addition, 10Ti alloy had a Moss + T2 + (Mo, Ti)2C eutectic. There was no Moss + T2 + (Mo, Ti)2C eutectic in the 15Ti alloy, and thus it is apparent that the (Mo, Ti)2C formation was suppressed by 5 at. % Ti addition. The volume fraction of (Ti, Mo)C increased and thus the density reduced from 8.78 to 8.43 g/cm3 with the Ti addition. In all constituent phases, Ti concentration increased while Mo concentration decreased. In spite of the changes, hardness, Young’s modulus and shear modulus were hardly changed. Therefore, Ti addition seems to be effective to further lower the density without deteriorating mechanical properties of the MoSiBTiC alloy.